Boundary-value problems with random initial conditions and functional series from subφ (Ω). II - Koval’chuk, Yu. A.; Kozachenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We study conditions for convergence and the rate of convergence of random functional series from the space subφ(Ω) in various norms. The results obtained are applied to the investigation of a boundary-value problem for a hyperbolic equation with random initial conditions.